Comparison of the Effectiveness of Moral Cognitive Education and Moral Action Education on the Responsibility of Female Students with a Positive Attitude Towards Academic Cheating - Fallahpour, Maryam; Hassanzadeh, Ramezan; Emadian, Seyedeh Olia (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective:  This study aims to answer whether there is a difference between moral cognitive education and moral action education on the responsibility of female students with a positive attitude towards academic cheating.Methods and Materials: The research method was semi-experimental, with a pretest-posttest and follow-up design with a control group. The statistical population of this study included all second-grade high school female students in Sari city who were studying in the academic year 2021-2022. The sample size was calculated to be 45 students using multistage cluster sampling. With random assignment, 15 students were allocated to experimental group A (related to moral cognitive education), 15 students to experimental group B (related to moral action education), and 15 students to group C (control). The Namati Responsibility Questionnaire (2008) was used. For data analysis, descriptive statistics and inferential statistics (repeated measures ANOVA and Bonferroni post hoc test) were performed using SPSS version 24.Findings: According to the results obtained from Chapter Four, in the variables of self-management, discipline, lawfulness, conscientiousness, organization, and progressiveness, no significant difference was observed between the moral cognitive education group and the moral action education group throughout the study. The difference was significant between the control group with moral cognitive education and the control with moral action education. However, in the variable of trustworthiness, a significant difference was observed between the moral cognitive education group and the moral action education group throughout the study.Conclusion: Moral cognitive education and moral action education had an impact on the responsibility of female students with a positive attitude towards academic cheating and led to a high level of responsibility among students.